Stringency and Distribution in the EU Emissions Trading Scheme The 2005 Evidence - Stefan P. Schleicher; Claudia Kettner; Angela Köppl; Gregor Thenius (Fondazione Eni Enrico Mattei (FEEM), 2007)
With the release of the verified emissions for installations covered by the EU Emissions Trading Scheme for the first trading year 2005 we are able to compare actual emissions and allowances for each installation. Based on data available for 24 Member States as of January 2007, this paper uses a thorough data analysis for about 9,900 installations to investigate evidence on three issues: first, the stringency of the total allocation cap and allocation differences both among the Member States and a selection of emission intensive sectors; second, the distribution of the size of installations; and third, the spread of allocation discrepancies and possible allocation biases regarding the size of installations.
Keywords: D61; O1; Q51; Q54; 330; Emission Trading; EU Emissions Trading Scheme; Climate Policy; Klimaschutz; Emissionshandel; EU-Staaten